2016
DOI: 10.1002/dta.2031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hepatic cytochrome P450 enzymes involved in the metabolism of 25I‐NBOMe and 25I‐NBOH

Abstract: The dimethoxyphenyl-N-((2-methoxyphenyl)methyl)ethanamine (NBOMe) compounds are potent serotonin 5-HT2A receptor agonists and have recently been subject to recreational use due to their hallucinogenic effects. Use of NBOMe compounds has been known since 2011, and several non-fatal and fatal intoxication cases have been reported in the scientific literature. The aim of this study was to determine the importance of the different cytochrome P450 enzymes (CYP) involved in the metabolism of 2-(4-iodo-2,5-dimethoxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Given the small number of samples in both studies, individual differences, such as enzyme polymorphisms, might have played a role. This would be consistent with Nielsen et al’s findings that equal amounts of the 2’‐ and 5’‐desmethyl metabolite are found in pooled HLM, but different amounts in incubations with recombinant CYP enzymes, namely CYP2C9, CYP2D6 and CYP3A4 . For 25B‐NBOMe, Leth‐Petersen et al showed dominance of the 5’‐desmethyl metabolite .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Given the small number of samples in both studies, individual differences, such as enzyme polymorphisms, might have played a role. This would be consistent with Nielsen et al’s findings that equal amounts of the 2’‐ and 5’‐desmethyl metabolite are found in pooled HLM, but different amounts in incubations with recombinant CYP enzymes, namely CYP2C9, CYP2D6 and CYP3A4 . For 25B‐NBOMe, Leth‐Petersen et al showed dominance of the 5’‐desmethyl metabolite .…”
Section: Discussionsupporting
confidence: 89%
“…In vitro incubation with human liver microsomes (HLM), cytosol, S9 fraction or recombinant CYP isoenzymes confirmed the main phase I reactions. Presence of the 2’‐ and 5’‐desmethyl 25I‐NBOMe and 4‐hydroxy 25I‐NBOMe was later confirmed with a reference standard . A 25I‐NBOMe metabolism study in fresh mouse liver microsomes and two human urine specimens identified 15 metabolites .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The ions detected at m/z 107.0491 and 308.0142 are produced by the cleavage of the C–N bond corresponding to o-cresol and 2C-I, respectively. The ion recorded at m/z 290.9876 is formed after the loss of the amine from the 2C-I fragment [9], and it corresponds to the most abundant ion in the CID spectrum of 25I-NBOH. The presented results suggest that 2C-I ( m/z 308.0142) is a fragment of the 25I-NBOH, explaining the presence of this compound in the high-energy production spectra of this drug.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…[14] After 10 min of pre-incubation of the compound with pHLM, the reactions were then started by addition of the NADPH regenerating system consisting of Glucuronidation in pHLM was investigated by following a previously published procedure. [15] Here, the enzymatic reactions were commenced by the addition of UDPGA and alamethicin at the final concentrations of 2 mM and 25 µg/mL, respectively, with and without presence of NADPH.…”
Section: Human Liver Microsomal Incubationmentioning
confidence: 99%